Factor structure and psychometric properties of the brief illness perception questionnaire in Turkish cancer patients - Tuğba Karatas; Sükrü Özen; Sevinç Kutlutürkan (Asia-Pacific Journal of Oncology Nursing, 2017)
Objective: The main aim of this study was to investigate the factor structure and psychometric properties of the Brief Illness Perception Questionnaire (BIPQ) in Turkish cancer patients. Methods: This methodological study involved 135 cancer patients. Statistical methods included confirmatory or exploratory factor analysis and Cronbach alpha coefficients for internal consistency. Results: The values of fit indices are within the acceptable range. The alpha coefficients for emotional illness representations, cognitive illness representations, and total scale are 0.83, 0.80, and 0.85, respectively. Conclusions: The results confirm the two-factor structure of the Turkish BIPQ and demonstrate its reliability and validity.